2013
DOI: 10.1002/swe.20056
|View full text |Cite
|
Sign up to set email alerts
|

Community‐wide validation of geospace model ground magnetic field perturbation predictions to support model transition to operations

Abstract: [1] In this paper we continue the community-wide rigorous modern space weather model validation efforts carried out within GEM, CEDAR and SHINE programs. In this particular effort, in coordination among the Community Coordinated Modeling Center (CCMC), NOAA Space Weather Prediction Center (SWPC), modelers, and science community, we focus on studying the models' capability to reproduce observed ground magnetic field fluctuations, which are closely related to geomagnetically induced current phenomenon. One of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
336
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(342 citation statements)
references
References 94 publications
(103 reference statements)
4
336
2
Order By: Relevance
“…The approach is interesting as it allows to identify systematic deficiencies across models. In practical terms this also means assistance of community wide model validation efforts (e.g., Pulkkinen et al, 2013;Rastätter et al, 2014;Glocer et al, 2016;Welling et al, 2017). SWP here is a trend setter.…”
Section: Model Developmentmentioning
confidence: 99%
“…The approach is interesting as it allows to identify systematic deficiencies across models. In practical terms this also means assistance of community wide model validation efforts (e.g., Pulkkinen et al, 2013;Rastätter et al, 2014;Glocer et al, 2016;Welling et al, 2017). SWP here is a trend setter.…”
Section: Model Developmentmentioning
confidence: 99%
“…Finally, ground magnetometer observations are used to validate several global models of geospace dynamics for both research and forecast purposes (e.g., Pulkkinen et al, 2013;Shi et al, 2008;Weygand et al, 2011;Yu & Ridley, 2008). The increasing demand for such comparisons again requires the prompt dissemination of all ground magnetometer data, as well as additional higher-level data products.…”
Section: Scientific Value Of Ground Magnetometer Arrays For Space Weamentioning
confidence: 99%
“…This single example shows (but does not prove in general) that a more sophisticated model can provide better agreement with measurements. In a recent study, requested by the U.S. national Space Weather Prediction Center (SWPC), Pulkkinen et al (2013) compared several empirical and physics based magnetosphere models for several geomagnetic events and found that the SWMF using the coupled BATS-R-US, RCM and RIM models consistently outperformed all the empirical models as well as the global MHD models that were not coupled with an inner magnetosphere model, and in fact the SWMF has been selected to be transitioned to operations at NOAA's Space Weather Prediction Center (SWPC).…”
Section: Using Simulations To Accurately Capture Magnetosphere Structmentioning
confidence: 99%